Global trends in Phoebe germplasm exploration: perspective of threatened tree species ecology and sustainability - Beibei Chen; Yuan Li; Zhongbiao Ding; Zhenqi Liao; Yingxuan Luo; Boon Chin Tan; Chee How Teo (Journal for Nature Conservation, 2026)

Genome-wide identification of sORFs in Oryza sativa subsp. indica and their comparative transcriptomic analysis under stress - Sheue Ni Ong; Boon Chin Tan; Kousuke Hanada; Hui Zhao; Chee How Teo (Plant Biosystems, 2026)

Bioclimatic drivers and niche Thresholds: Decoupling the habitat suitability dynamics of Phoebe zhennan - Beibei Chen; Weiyi Liu; Zhenqi Liao; Yuan Li; Zhongbiao Ding; Yingxuan Luo; Boon Chin Tan; Chee How Teo (Journal for Nature Conservation, 2026)

CircRNA expression profiling in H1N1-infected primary human tracheobronchial epithelial cells identifies candidate immune-related circRNAs validated in A549 cells - Kai Shen Lim; Mathanakumara Ealam Selvan; Chee-Kwee Ea; Chee How Teo; Yat-Yuen Lim (Archives of Virology, 2026)

Whole Genome Assembly, Annotation, and Comparative Genomic Analysis of Pandanus amaryllifolius - Norhafizah Sidek; Boon Chin Tan; Katharina Mebus; Shinji Kikuchi; Chee How Teo (Plant Molecular Biology Reporter, 2025)

The regulatory role of phytohormones in plant drought tolerance - Zhenqi Liao; Beibei Chen; Hatem Boubakri; Muhammad Farooq; Luis Alejandro Jose Mur; Daisuke Urano; Chee How Teo; Boon Chin Tan; MD Mahadi Hasan; Mehtab Muhammad Aslam; Muhammad Yahya Tahir; Junliang Fan (Planta, 2025)

Pandanus amaryllifolius transcriptome under drought stress reveals differential expression profile of genes related to plant hormone signal transduction and MAPK signaling pathways - Sidek Norhafizah; Boon Chin Tan; Taheri Sima; Mebus Katharina; Chee How Teo (Brazilian Journal of Botany, 2025)

Establishment of effective plantlets regeneration protocol via isolated microspore culture in Malaysian indica rice MR219 - Zuraida Abd Rahman; Zulkifli Ahmad Seman; Ayu Nazreena Othman; Mohamad Bahagia Ab Ghaffar; Shahril Ab Razak; Muhammad Fairuz Mohd Yusof; Khairun Hisam Nasir; Khairulmazmi Ahmad; Yeow Lit Chow; Teo Chee How; Norsharina Md Saad; Sreeramanan Subramaniam (Plant Biotechnology Reports, 2022)

Viral disease of tomato crops (Solanum lycopesicum L.): an overview - Sheue Ni Ong; Sima Taheri; Rofina Yasmin Othman; Chee How Teo (Journal of Plant Diseases and Protection, 2020)

Detection of somaclonal variations in tissue cultured date palm (Phoenix dactylifera L.) using transposable element-based markers - Abdul Aziz Mirani; Chee How Teo; Ghulam Sarwar Markhand; Adel Ahmed Abul-Soad; Jennifer Ann Harikrishna (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

Differential gene expression analysis of Secreted in Xylem (SIX) genes from Fusarium oxysporum f. sp. cubense tropical race 4 in Musa acuminata cv. Berangan and potential application for early detection of infection - Nee Kiew Poon; Chee How Teo; Rofina Yasmin Othman (Journal of General Plant Pathology, 2020)

Evaluation of banana germplasm and genetic analysis of an F1 population for resistance to Fusarium oxysporum f. sp. cubense race 1 - Ivan Kabiita Arinaitwe; Chee How Teo; Fatimah Kayat; Robooni Tumuhimbise; Brigitte Uwimana; Jerome Kubiriba; Rony Swennen; Jennifer Ann Harikrishna; Rofina Yasmin Othman (Euphytica, 2019)
Fusarium wilt of bananas ( Musa spp.), caused by Fusarium oxysporum f. sp. cubense ( Foc ) causes up to 100% yield loss in bananas. Foc race 1 in particular is very devastating to dessert bananas in Uganda. One of the effective control strategies for the disease is the development of resistant cultivars through breeding. The objectives of this study were to identify suitable banana germplasm for generating a segregating population for resistance to Foc race 1 and understand the mode of inheritance of resistance to Foc race 1. Twenty-two banana accessions sourced from the National Agricultural Research Organisation in Uganda were challenged with Foc race 1 in a screen house experiment. Monyet, resistant to Foc race 1 and Kokopo, susceptible, were selected and crossed to generate 142 F 1 genotypes. These F 1 genotypes were also challenged with Foc race 1 in a screen house experiment. Data were collected on rhizome discoloration index (RDI), leaf symptom index (LSI) and pseudo-stem splitting (PSS), and analysed for variability. The banana accessions evaluated showed varying degrees of resistance to Foc race 1. Segregation ratios for resistant versus susceptible progenies fitted 13:3 (χ 2 = 0.12, P = 0.73) for RDI and 11:5 (χ 2 = 3.04, P = 0.08) for PSS. Estimated broad sense heritability was 27.8% for RDI, 13.9% for LSI and 14.7% for PSS. The results suggest that resistance to Foc race 1 in banana is controlled by at least two dominant genes with epistatic interaction and that heritability of resistance to Foc race 1 is low in Musa spp.

Comparative analysis of Argonaute gene sequences in bananas (Musa sp.) shows conserved species-specific Ago-7 PIWI domains - Chee How Teo; Han Pin Pui; Rofina Yasmin Othman; Jennifer Ann Harikrishna (Genetic Resources and Crop Evolution, 2011)

Genome classification of banana cultivars from South India using IRAP markers - Ashalatha S. Nair; Chee How Teo; Trude Schwarzacher; Pat Heslop Harrison (Euphytica, 2005)

Genome constitution and classification using retrotransposon-based markers in the orphan crop banana - Chee How Teo; Siang Hee Tan; Chai Ling Ho; Qamaruz Zaman Faridah; Yasmin Rofina Othman; John Seymour Heslop-Harrison; Ruslan Kalendar; Alan Howard Schulman (Journal of Plant Biology, 2005)